2021
DOI: 10.4103/joco.joco_42_20
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Posterior Segment Syndrome Presenting as Occlusive Retinal Vasculitis Following Vitreoretinal Surgery

Abstract: Purpose: To report a rare retinal manifestation of toxic posterior segment syndrome following vitreoretinal surgery. Methods: In this case series, we report three cases of rhegmatogenous retinal detachment for which pars plana vitrectomy with silicone oil injection was done. All three patients developed an intense anterior chamber reaction along with occlusive vasculitis-like fundus picture. Results: The three patients were started on topical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The possible mechanisms of silicone oil induced toxicity include a direct immunogenicity to the components such as ionic compounds, cleavable fluoride present in silicone oil, direct toxicity of silicone oil, or emulsification of silicone oil. 10 Another case series reported by Sahoo et al, 11 reported toxic posterior segment syndrome presenting as occlusive retinal vasculitis due to silicone oil tamponade.…”
Section: Discussionmentioning
confidence: 97%
“…The possible mechanisms of silicone oil induced toxicity include a direct immunogenicity to the components such as ionic compounds, cleavable fluoride present in silicone oil, direct toxicity of silicone oil, or emulsification of silicone oil. 10 Another case series reported by Sahoo et al, 11 reported toxic posterior segment syndrome presenting as occlusive retinal vasculitis due to silicone oil tamponade.…”
Section: Discussionmentioning
confidence: 97%
“…[ 5 ] In literature, it is shown to be developed both after posterior segment surgeries with signs and symptoms of retinal vasculitis and a dropless cataract surgery. [ 5 - 7 ]…”
Section: Discussionmentioning
confidence: 99%